2009
DOI: 10.1007/s00276-009-0464-4
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical anatomy of the foramen of Luschka in the cerebellopontine angle, and its vascular supply

Abstract: Cerebellopontine angle and vascular supply of adjacent brainstem and cerebellum are susceptible to compression and eventual damage by tumors. Delicate and complicated neurosurgical operations in the cerebellopontine angles of the brainstem, where lateral recesses of fourth ventricle empty, are abundant especially operations in which foramina of Luschka are used as possible access to the floor of the fourth ventricle. So awareness and knowledge of the normal anatomical features of the region is valuable for neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…This result is consistent with the report by Nevoux that the feeding vessels often arise from branches of the external carotid artery (the posterior auricular artery) or ascending pharyngeal artery and sometimes from branches of the vertebral artery (the anterior inferior cerebellar artery). This finding can help us to distinguish ELST from CPP at the CPA region, the blood supply of which comes from the anterior inferior cerebellar artery …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This result is consistent with the report by Nevoux that the feeding vessels often arise from branches of the external carotid artery (the posterior auricular artery) or ascending pharyngeal artery and sometimes from branches of the vertebral artery (the anterior inferior cerebellar artery). This finding can help us to distinguish ELST from CPP at the CPA region, the blood supply of which comes from the anterior inferior cerebellar artery …”
Section: Discussionmentioning
confidence: 89%
“…This finding can help us to distinguish ELST from CPP at the CPA region, the blood supply of which comes from the anterior inferior cerebellar artery. 20,21 ELST arises in the epithelium of the endolymphatic sac ( Fig. 2E1)/duct which is the normal structure of the inner ear, goes through the bone suture and is surrounded by the dura mater.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to our study especially in elderly patients, Boc FBCs extend to 2 cm far from the center. This different result shows that tortious basilar and vertebral artery calcifications can overlap with Boc FBCs in the cerebellopontine angle [15]. Bradac et al found symmetry between two sides of the choroid plexuses of the fourth ventricle in 96.5% of 57 brain dissections [16].…”
Section: Sharifi Et Al Divided the Boc Fbc Into Two Parts Which Is Si...mentioning
confidence: 97%
“…is description was ratified by Sharifi et al 6 years later. [7,14] Choroidal compartment of FOL e choroid plexus of the fourth ventricle has T-shaped distribution. Its lateral horizontal section sits laterally in the lateral recess and protrudes outside the FOL, the so-called Bochdalek's flower basket (BFB) [Figure 2].…”
Section: Ventricular Side Of Folmentioning
confidence: 99%